Physiological monitoring system for high altitude sports - Ridolfi, A.; Vetter, R.; Sola, J.; Sartori, C. (Procedia Engineering, 2010)
Improvement of sport performances at high altitude would require the monitoring of physiological parameters such as heart rate, SpO2, and respiration. However, commercially available devices cannot cope with peculiar measurements conditions, e.g., cold temperatures exclude the use of fingertip/earlobe SpO2 probes and movement artifacts require specific signal enhancement algorithms. We present a new non-invasive monitoring system ergonomically integrated into a T-shirt: It includes 3 multiparameter active dry-electrodes, a data-logger storing and transmitting data, and new processing algorithms reducing artifacts and enhancing signals. A series of tests in controlled conditions demonstrate that a more reliable estimate of the targeted parameters can be achieved. These data strongly suggest the potential advantages of our system to provide insight into high altitude adaptation, planning of training sessions in active subjects exposed to high altitude.